Organising for a Changing Europe? Irish Central Government and the European Union - Laffan, Brigid (Trinity College Dublin, 2001)
Organising for a Changing Europe? Irish Central Government and the European Union examines the management of EU policy in Ireland from the perspective of central government. The research was undertaken in response to Ireland?s changing position in the EU and the changing dynamic of public policy making in the European Union. The author uses the lens of co-ordination to identify the strengths and weaknesses of the Irish system. The analysis includes six government departments and the wider mechanisms for managing EU business across the system, including committees, departmental co-ordination units and a Minister for European Affairs. The study includes a brief comparison with the Netherlands and Finland, two member states with much more formalised systems for managing EU business. The paper concludes with a series of recommendations.
Keywords: Public Policy; EU policy; Ireland